Pengaruh Pemahaman Pajak, Keadilan Pajak, Love of Money dan Religiusitas Terhadap Persepsi Mahasiswa Mengenai Penggelapan Pajak (Studi Kasus Mahasiswa di Universitas Muhammadiya Surabaya) - Pendalungan, Diah Surya; Nuraini, Fitri; Sa'diyah, Halimatus (SUSTAINABLE, 2024)
THE INFLUENCE OF TAX UNDERSTANDING, TAX JUSTICE, LOVE OF MONEY AND RELIGIOSITY ON STUDENTS’ PERCEPTIONS OF TAX EVASION (Case Study of Students at Muhammadiyah University of Surabaya) Diah Surya Pendalungan Accounting Study Programme FEB-Universitas Muhammadiyah Surabaya Email: diah.surya01@gmail.com ABSTRACT In Indonesia, tax evasion still often occurs among unscrupulous taxpayers who lack a sense of responsibility. It is an attempt by taxpayers to reduce the tax burden by violating applicable tax laws and regulations. This tax evasion occurs due to several factors, such as: tax understanding, tax justice, love of money and religiosity. This study aims to determine the relationship between the variables of tax understanding, tax justice, love of money and religiosity on tax evasion. This research method uses a quantitative approach with purposive sampling technique as many as 178 students. The measuring instrument used in this study is SPSS Version 25 software. The analysis method used in this research is multiple linear regression analysis. The results showed that (1) Tax understanding has a significant negative effect on tax evasion. (2) Tax justice has a significant negative effect on tax evasion. (3) Love of money has no significant effect on tax evasion. (4) Religiosity has no significant effect on tax evasion. Keywords: Tax understanding, tax justice, love of money, religiosity, students’ perceptions of tax evasion.